Electrochemical Utilization of Iron IV in the Li1.3Fe0.4Nb0.3O2 Disordered Rocksalt Cathode. Issue 5 (20th January 2021) - Lebens‐Higgins, Zachary; Chung, Hyeseung; Temprano, Israel; Zuba, Mateusz; Wu, Jinpeng; Rana, Jatinkumar; Mejia, Carlos; Jones, Michael A.; Wang, Le; Grey, Clare P.; Du, Yingge; Yang, Wanli; et al.
Abstract: Interest in alkali‐rich oxide cathodes has grown in an effort to identify systems that provide high energy densities through reversible oxygen redox. However, some of the most promising compositions such as those based solely on earth abundant elements, e. g., iron and manganese, suffer from poor capacity retention and large hysteresis. Here, we use the disordered rocksalt cathode, Li1.3 Fe0.4 Nb0.3 O2, as a model system to identify the underlying origin for the poor performance of Li‐rich iron‐based cathodes. Using elementally specific spectroscopic probes, we find the first charge is primarily accounted for by iron oxidation to 4+ below 4.25 V and O2 gas release beyond 4.25 V with no evidence of bulk oxygen redox. Although the Li1.3 Fe0.4 Nb0.3 O2 is not a viable oxygen redox cathode, the iron 3+/4+ redox couple can be used reversibly during cycling. Abstract : Degradation threshold : For the Li‐excess Li1.3 Fe0.4 Nb0.3 O2 disordered rocksalt cathode, the high capacity is identified to result from iron redox to 4+ and cathode degradation. Iron redox accounts for the capacity on continued cycling and there is no reversible lattice oxygen redox. By limiting the upper cutoff voltage to avoid cathode degradation, the capacity retention is greatly improved associated with reversible utilization of iron redox.